177 FLUCTUATING ASYMMETRY: RELATIONSHIP TO DURATION AND CAUSE OF LOW BACK PAIN - Bonman, S.; Vu, N.; Martin, J. T. (Journal of investigative medicine, 2007)
Previous studies have shown that in utero stressors can lead to developmental instability (DI). This DI can possibly predispose to disease susceptibility later in life. A composite of differences in bilateral anatomic trait measurements is termed fluctuating asymmetry (FA) and serves as an indicator of DI. Evidence from our laboratory has pointed to the ulna as abnormally symmetric in persons with chronic low back pain (LBP) but not in persons with acute LBP. It was unclear from the previous study whether the duration and the severity of LBP was a factor in this abnormal asymmetry. To explore these questions we examined the relationship between FA in event-related and non-event-related causes of the LBP, which were further classified according to pain severity. A severity index was developed based on frequency of treatment for LBP. Ulna, lower arm, hand width, hand length, wrist width, and third proximal phalange lengths were measured in 109 patients with LBP and 122 controls in four hospitals and clinics in Southern California. Information on the duration and cause of the LBP was obtained by questionnaire. We postulated that the highest incidence of FA would be found in subjects with chronic LBP stemming from non-event-related causes, which might be due to developmental errors. Furthermore, we suspected that the severity of LBP would be directly related to the size of FA. Our results indicated that persons with LBP of more than 6 months' duration had significant rightward asymmetry in the ulna (p = .04) and a trend to rightward asymmetry in the composite of six hand and arm traits (p = .056). Results indicated no difference between event-related causes, non-event-related causes, and control FA of the ulna. We also found no significant relationship between the LBP severity index and measures of FA or of directional asymmetry. These findings support the results in the previous study showing elevated rightward directional asymmetry in chronic LBP patients. Although our data do not support a relationship between ulnar asymmetry and cause and severity of LBP, other traits, not yet analyzed, may demonstrate such a relationship.